Pharmacokinetics of the evogliptin/metformin extended-release (5/1,000 mg) fixed-dose combination formulation compared to the corresponding loose combination, and food effect in healthy subjects - Rhee SJ; Lee S; Yoon SH; Cho JY; Jang IJ; Yu KS (Dove Medical Press, 2016)
Su-jin Rhee,1,* SeungHwan Lee,1,2,* Seo Hyun Yoon,1 Joo-Youn Cho,1 In-Jin Jang,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 2Clinical Trials Center, Seoul National University Hospital, Seoul, Republic of Korea *These authors contributed equally to this work Abstract: A new fixed-dose combination formulation of evogliptin 5 mg and metformin extended-release (XR) 1,000 mg (FDC_EVO5/MET1000) was developed to improve medication adherence for type 2 diabetes mellitus. The pharmacokinetics of FDC_EVO5/MET1000 was compared to the corresponding loose combination in a randomized, open-label, crossover study in 36 healthy male subjects (Part 1), and the food effect on FDC_EVO5/MET1000 was assessed (under fasted or fed conditions) in a randomized, open-label, crossover study in 28 healthy male subjects (Part 2). Serial blood samples for pharmacokinetic analysis were collected up to 72 hours, and pharmacokinetic parameters of evogliptin and metformin were calculated using non-compartmental methods. The geometric mean ratios (fixed-dose combination to loose combination) and 90% confidence intervals of pharmacokinetic parameters for evogliptin and metformin were all within 0.800–1.250, suggesting bioequivalent pharmacokinetic. After a single oral dose of FDC_EVO5/MET1000, food did not significantly affect evogliptin pharmacokinetic while systemic exposure of metformin was increased about 47.5% under the fed condition, which is consistent with the already established food effect on metformin XR. FDC_EVO5/MET1000 was generally well tolerated without any drug-related serious adverse events. In conclusion, FDC_EVO5/MET1000 can be substituted for the loose combination of FDC_EVO5/MET1000, providing better compliance with convenient administration. Keywords: pharmacokinetics, bioequivalence, food effect, fixed-dose combination, evogliptin, metformin XR